2013
DOI: 10.1149/2.019311jes
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrolyte Additives of Phosphate, Carbonate, and Borate to Improve Redox Capacitor Performance of Manganese Oxide Electrodes

Abstract: For a faradaic electrochemical capacitor, birnessite-based manganese dioxide electrode, prepared by the electrochemical activation of ball-milled Mn 3 O 4 composite electrodes as we recently reported, delivers 190 F g −1 in a Na 2 SO 4 aqueous solution in the potential range of −0.1 and 0.9 V vs. Ag/AgCl at a current rate of 1.0 A g −1 . However, the specific capacitance of birnessite gradually decreases during successive charge and discharge cycle, and the capacity decrease is accompanied by the gradual loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Various factors of the neutral electrolytes, such as pH, the types of cation and anion species, 117 salt concentrations, [118][119][120] additives, 121,122 and solution temperatures, have been found to have an influence on the ES performance. Various factors of the neutral electrolytes, such as pH, the types of cation and anion species, 117 salt concentrations, [118][119][120] additives, 121,122 and solution temperatures, have been found to have an influence on the ES performance.…”
Section: Neutral Electrolytes For Pseudocapacitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Various factors of the neutral electrolytes, such as pH, the types of cation and anion species, 117 salt concentrations, [118][119][120] additives, 121,122 and solution temperatures, have been found to have an influence on the ES performance. Various factors of the neutral electrolytes, such as pH, the types of cation and anion species, 117 salt concentrations, [118][119][120] additives, 121,122 and solution temperatures, have been found to have an influence on the ES performance.…”
Section: Neutral Electrolytes For Pseudocapacitorsmentioning
confidence: 99%
“…121 For example, Komaba et al 121 found that upon addition of a small amount of Na 2 HPO 4 , NaHCO 3 , or Na 2 B 4 O 7 into the Na 2 SO 4 electrolyte, the specific capacitance of the birnessite electrode could be increased from 190 F g À1 to 200-230 F g À1 at 1.0 A g À1 , and at the same time the cyclability was also significantly improved (41000 cycles). 121 For example, Komaba et al 121 found that upon addition of a small amount of Na 2 HPO 4 , NaHCO 3 , or Na 2 B 4 O 7 into the Na 2 SO 4 electrolyte, the specific capacitance of the birnessite electrode could be increased from 190 F g À1 to 200-230 F g À1 at 1.0 A g À1 , and at the same time the cyclability was also significantly improved (41000 cycles).…”
Section: Neutral Electrolytes For Pseudocapacitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since negatively charged buffer ions (e.g., phosphate, carbonate, and borate) can create an insoluble layer on the surface of MnO 2 combined with Mn 2+ , it is likely that regulating both H + and Mn 2+ contributes to the improvement. 32 To determine how the solution pH was influenced by the redox reaction of MnO 2 (i.e., H + insertion/deinsertion), we measured the effluent pH from the anode (oxidation) and cathode (reduction) compartments of a 2-channel flow cell divided by a CEM. The anode effluent pH decreased from 8 to 4 in the absence of phosphate (Figure 2a), which was attributed to H + deinsertion upon oxidation (Figure 2b).…”
Section: ■ Introductionmentioning
confidence: 99%